Antioxidant response of the invasive herb Ambrosia artemisiifolia L. to different irradiance levels - Qin, Zhong; Mao, DanJuan; Quan, GuoMing; Zhang, Jia-En; Xie, JunFang; DiTommaso, Antonio (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ), 2013)
The exotic invasive Ambrosia artemisiifolia L. and a native co-occurring species in southern China, Urena lobata L., were compared to investigate the possible protective role of leaf antioxidant systems in the acclimation of invasive plants to different irradiance levels. Antioxidant activities of superoxide dismutase (SOD), peroxidase (POD), and catalase (CAT) were examined under four irradiance regimes: 10% (dense shade), 30% (low irradiance), 55% (medium irradiance) and 100% (full irradiance). Free proline (Pro) content and the rate of lipid peroxidation in terms of malondialdehyde (MDA) content, glutathione reductase (GR), and tea polyphenols (TP) were also assessed under the different irradiance regimes. Antioxidant enzyme activity of SOD and CAT and the MDA, GR and TP contents for the two species increased with increasing irradiance levels. Invasive A. artemisiifolia was able to scavenge oxygen radicals more efficiently at higher irradiance levels by enhancing CAT activity and GR and TP contents although leaf SOD activity was not greatly enhanced. This exotic species also maintained normal physiological functions when subjected to low irradiance, which might be attributed to the increase in POD activity with decreasing irradiance levels. The higher efficiency of adaptive responses of antioxidant enzymes may protect plants from irradiance-induced stress and may contribute to the invasiveness of A. artemisiifolia in subtropical and tropical regions.